VISUAL PROPERTIES COMPOSITION ECO HOTEL (WORLD EXPERIENCE) - , В. А., Е. А. (Municipal economy of cities. Series: «Economy science», 2016)
Comfortable visual environment provides favorable terms which necessary for the manifestation of physiological mechanisms of view. Properly organized manufactured environment is always closest to the natural. One method of forming a comfortable environment in the architecture is the nature of similarity of its forms. Objects architecture should please the human eye, only then they will have a positive impact on him, his health and on the environment as a whole. Keywords: perception, environment, architecture, space, experience, rating.